Empowering Filipino women seafarers in the maritime sector - Tangi, Lucia P. (Public Policy, 2016)
Filipinos account for a quarter of the world's 1.6 million seafarers. However, Filipino women account for only around two percent of more than 400,000 seafarers deployed annually. Around 90 percent of these women seafarers are in the services and domestic sectors, doing jobs that are related to their reproductive duties. Because of this, Filipino women seafarers are among the lowest paid in the seafaring industry, and are also among the most vulnerable to redundancy. Following the enactment in the 1990s of the Women in Development and Nation Building Act, maritime schools started opening up to women who wanted to become sea officers. Although more women have been attracted to seafaring in the past decade, the number of women sea officers has remained microscopic, compared to the thousands of male sea officers deployed every year. Based on focus group discussions and key informant interviews with almost a hundred stakeholders, this study finds that women sea officers often face discrimination as soon as they start applying for shipboard internship and employment. They have to battle loneliness, sexual harassment, and bullying by their male colleagues on board. This study finds that patriarchal beliefs and control in the seafaring industry have discouraged women sea officers from pursuing careers at sea. This is aggravated by the race among ship owners to reduce costs, at the expense of seafarers. Using the women's empowerment framework developed by Sara Longwe and the human rights-based approach as guides, this policy research paper proposes a package of measures to empower women by addressing issues on welfare, access, conscientization, mobilization and control in the maritime industry.